SOME THOUGHTS ON THE IMPORTANCE OF FOREIGN INVESTMENT IN INCREASING THE INVESTMENT ATTRACTIVENESS OF UZBEKISTAN - Xabibullayev Baxtiyor Abdulvoxid o’g’lii (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Modern Uzbekistan is the leading industrial state in the Central Asian region, ensuring stability and economic development of the region as a whole. Among the advantages offered by the modern economy of Uzbekistan for foreign companies are political and macroeconomic stability, favorable natural and climatic conditions, hospitable and hardworking people and many others.